Kewajiban Notaris Dalam Melaksanakan Peraturan Menteri Hukum dan Ham tentang Penerapan Prinsip Mengenali Pengguna Jasa Bagi Notaris - Qonitah Annur Aziza; Ferina Yola Damayanti; Indrawati (Fakultas Hukum Universitas Airlangga, 2022)
AbstractNotary has an obligation to keep the deeds that have been regulated in the Code of Ethics and Article 4 UUJN-P jo. Article 16 paragraph (1) letter f UUJN-P. To prevent and eradicate money laundering crime, a Notary is appointed as one of the Reporting Parties who is obliged to apply the Principle of Recognizing Service Users which is specifically regulated in Permenkumham 9 of 2017. There is also need for legal protection to Notaries as positions appointed by the government and the Reporting Parties in order to avoid legal snares that harm Notaries. The writing of this article uses a normative type of research by reviewing applicable laws and regulations as well as theoretical studies from the existing literature. This research is based on the analysis of laws and regulations related to the legal ratio of Permenkumham 9 of 2017 and legal protection for Notaries. The approach used are the statutory approach, conceptual approach and case approach. All legal materials that have been collected and inventoried will then be processed and studied in depth. The result of this research is that the enactment of Permenkumham 9 of 2017 has a purpose for the interest of the state not individuals and also the protection of Notaries as position regulated in Article 50 of the Criminal Code and as a reporting party protected by Article 28 and Article 29 of the Money Loundering Law.Keywords: Reporting Party; Principles of Recognizing Service Users; Legal Protection. AbstrakNotaris memiliki kewajiban untuk merahasiakan akta yang telah diatur dalam Kode Etik dan Pasal 4 UUJN-P jo. Pasal 16 ayat (1) huruf f UUJN-P. Untuk mencegah dan memberantas tindak pidana pencucian uang maka Notaris ditunjuk sebagai salah satu Pihak Pelapor yang wajib menerapkan Prinsip Mengenali Pengguna Jasa yang secara khusus diatur dalam Permenkumham 9 Tahun 2017. Perlunya pula perlindungan hukum bagi Notaris sebagai jabatan yang ditunjuk pemerintah dan Pihak Pelapor agar terhindar dari jerat hukum yang merugikan Notaris. Penulisan artikel ini menggunakan tipe penelitian normatif dengan mengkaji perundang-undangan dan peraturan yang berlaku juga kajian teoritis dari literaturyang ada. Penelitian ini bertitik tolak terhadap analisis peraturan perundangan terkait rasio legis Permenkumham 9 Tahun 2017 dan perlindungan hukum bagi Notaris. Pendekatan yang digunakan adalah pendekatan perundang-undangan, pendekatan konseptual dan pendekatan kasus. Semua bahan-bahan hukum yang telah dikumpulkan dan diinventarisasi tersebut kemudian akan diolah dan dikaji secara mendalam. Hasil dari penelitian ini adalah diberlakukannya Permenkumham 9 Tahun 2017 memiliki tujuan demi kepentingan negara bukan individu dan juga perlindungan Notaris sebagai jabatan diatur dalam Pasal 50 KUHP dan sebagai Pihak pelapor dilindungi dengan Pasal 28 dan Pasal 29 UU PPTPPU.Kata Kunci: Pihak Pelapor; Prinsip Mengenali Pengguna Jasa; Perlindungan Hukum.